Long non-coding RNA HIF1A-AS2 modulates the proliferation, migration, and phenotypic switch of aortic smooth muscle cells in aortic dissection via sponging microRNA-33b. Issue 3 (1st March 2022) - Zhang, Kai; Qi, Yujuan; Wang, Meng; Chen, Qingliang
ABSTRACT: Aortic dissection (AD), also known as aortic dissecting aneurysm, is one of the most common and dangerous cardiovascular diseases with high morbidity and mortality. This study was aimed to investigate the functional role of long non-coding RNA Hypoxia-inducible factor 1 alpha-antisense RNA 2 (lncRNA HIF1A-AS2) in AD. An in vitro model of AD was established by platelet-derived growth factor-BB (PDGF-BB)-mediated human aortic Smooth Muscle Cells (SMCs). HIF1A-AS2 expression in human AD tissues was determined by quantitative real-time PCR (qRT-PCR) and fluorescence in situ hybridization (FISH) assays, followed by investigation of biological roles of HIF1A-AS2 in AD development by Cell Counting Kit-8 (CCK-8), immunofluorescence, and transwell assays. Additionally, the correlation between HIF1A-AS2, miR-33b, and high mobility group AT-hook2 (HMGA2) were identified by RNA immunoprecipitation (RIP), RNA pull-down and luciferase reporter assays. Results showed that HIF1A-AS2 was obviously increased, while the contractile-phenotype markers of vascular SMCs were significantly decreased in human AD tissues, when compared to normal tissues. Inhibition of HIF1A-AS2 attenuated SMCs proliferation and migration, whereas enhanced the phenotypic switch under the stimulation of PDGF-BB. Results from RIP, RNA pull-down and luciferase reporter assays demonstrated that miR-33b directly bound with HIF1A-AS2, and HIF1A-AS2 silencing suppressed the expression of HMGA2, which was induced by miR-33b inhibitor. In conclusion, knockdown of HIF1A-AS2 suppressed the proliferation and migration, while promoted the phenotypic switching of SMCs through miR-33b/HMGA2 axis, which laid a theoretical foundation for understanding the development of AD and shed light on a potential target for AD treatment. Graphical abstract: uf0001